(untitled) (AYUSHDHARA, 2020)
Ulcerative colitis is an idiopathic inflammatory bowel disease causing inflammation and ulcers in the rectum and colon. Ulcerative colitis affects approximately 5,00,000 individuals in US with an incidence of 8-12 per 1,00,000 population per year. It is manifested as ano-rectal bleeding with increased frequency of bowel evacuation, general debility. In the contemporary science treatment is Corticosteroids, 5-Aminosalicylates, Anti-TNF therapy which results in other complications and the disease may even relapse after a period of time. A 62 years old female Patient attended OPD with diffuse abdominal pain, loose stools 10-15 times a day with blood, debility and weight loss. Patient was known case of ulcerative colitis since 6 years receiving treatment from contemporary science but she was not getting any satisfactory relief. Patient was treated with the concept of Pittaja Grahani in Ayurveda. Objective: To improve the signs and symptoms of the ulcerative colitis, to prevent from all possible intestinal and extra-intestinal complications related to ulcerative colitis finally to cure the disease. Method: Musta-Takra Basti was administered for 16 days along with other Ayurvedic drugs and signs and symptoms were evaluated daily. Result: Patient responded well with much improvement in her general condition. Frequency of defecation is decreased, no bleeding per rectum and other signs and symptoms were relieved. Conclusion: This study can be useful for reducing the need of steroids and surgical procedures in the patient of ulcerative colitis Hence Ayurveda treatment can be a promising alternative, safe and convenient treatment in the management of Ulcerative colitis.